SHADOWY USER BEHAVIOR IN DIGITAL MARKETING: A MANAGEMENT-ORIENTED VIEW ON CYBER POLICY, CULTURAL INFLUENCE, AND ONLINE INTERACTION - Arifah Rachmawati; Meiliyah Ariani (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
Online digital systems are driving the growth of economies, but they have also given rise to problematic online user behavior. Online shady practices are a threat to social cohesion, yet they persist and evade legal detection. To promote a healthy and inclusive digital environment, there is a need for further research to understand the interplay between culture, legislation, and online user behavior. This study aims to examine the interrelations between socio-cultural settings, cyber policies, and online user behavior. It explores the effectiveness of current policy measures and posits possible ways for promoting a healthy and inclusive digital environment. The study employs a narrative review of literature to understand the interplay between culture, legislation, and online user behavior. The findings highlight the influence of cultural settings on online user behavior and the interconnectedness of legislation, culture, and online interactions. The emphasis on the need for context-specific approaches and inclusive policymaking methodologies to foster a healthy and inclusive digital environment were the knowledge gaps identified that warrant further research. Understanding the interplay between cultural settings, legislation, and online user behavior provides valuable insights for practitioners and researchers to look more into a culturally sensitive safe digital space.